Ammonia electrosynthesis from nitrate using a stable amorphous/crystalline dual-phase Cu catalyst - Yi Wang; Shuo Wang; Yunfan Fu; Jiaqi Sang; Pengfei Wei; Rongtan Li; Dunfeng Gao; Guoxiong Wang; Xinhe Bao (Nature Communications)
Abstract Renewable energy-driven electrocatalytic nitrate reduction reaction presents a low-carbon and sustainable route for ammonia synthesis under mild conditions. Yet, the practical application of this process is currently hindered by unsatisfactory electrocatalytic activity and long-term stability. Herein we achieve high-rate ammonia electrosynthesis using a stable amorphous/crystalline dual-phase Cu catalyst. The ammonia partial current density and formation rate reach 3.33 ± 0.005 A cm−2 and 15.5 ± 0.02 mmol h−1 cm−2 at a low cell voltage of 2.6 ± 0.01 V, respectively. Remarkably, the dual-phase Cu catalyst can maintain stable ammonia production with a Faradaic efficiency of around 90% at a high current density of 1.5 A cm−2 for up to 300 h. A scale-up demonstration with an electrode size of 100 cm2 achieves an ammonia formation rate as high as 11.9 ± 0.5 g h−1 at a total current of 160 A. The impressive electrocatalytic performance is ascribed to the presence of stable amorphous Cu domains which promote the adsorption and hydrogenation of nitrogen-containing intermediates, thus improving reaction kinetics for ammonia formation. This work underscores the importance of stabilizing metastable amorphous structures for improving electrocatalytic reactivity and long-term stability.